Komitmen Organisasi Memediasi Antara Pengaruh Kepuasan Kerja dan Persepsi Lingkungan Kerja Terhadap Turnover Intention pada Karyawan PT.X Industri Pertambangan di Provinsi Kalimantan Selatan - Rendi Saputra; Hardani Widhiastuti; Rusmalia Dewi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of job satisfaction and perceptions of the work environment on turnover intention, with organizational commitment as an intervening variable, among employees of PT.X in the mining industry located in South Kalimantan Province. The study involved a total of 260 employee respondents. The sample was selected using simple random sampling. Data collection was conducted using four scales: turnover intention, organizational commitment, job satisfaction, and work environment perception. Data analysis was performed using the SmartPLS 4.0 program (2024). The results of the study indicate that job satisfaction significantly influences turnover intention, as evidenced by a p-value of 0.000<0.05. Perceptions of the work environment also significantly influence turnover intention, with a p-value of 0.029<0.05. Organizational commitment significantly affects turnover intention, with a p-value of 0.000<0.05. Furthermore, job satisfaction significantly influences organizational commitment, with a p-value of 0.000<0.05, and perceptions of the work environment significantly affect turnover intention, with a p-value of 0.000<0.05. The role of organizational commitment as a mediating factor is evident in the relationship between job satisfaction and turnover intention, showing a significant influence when mediated by organizational commitment. Similarly, organizational commitment mediates the relationship between perceptions of the work environment and turnover intention, demonstrating a significant effect among employees.